Iron-independent specific protein expression pattern in the liver of HFE-deficient mice - Petrak, Jiri; Myslivcova, Denisa; Halada, Petr; Cmejla, Radek; Cmejlova, Jana; Vyoral, Daniel; Vulpe, Christopher D (The international journal of biochemistry & cell biology, 2007)
Hereditary hemochromatosis type I is an autosomal-recessive iron overload disease associated with a mutation in HFE gene. The most common mutation, C282Y, disrupts the disulfide bond necessary for the association of HFE with beta-2-microglobulin and abrogates cell surface HFE expression. HFE-deficient mice develop iron overload indicating a central role of the protein in the pathogenesis of hereditary hemochromatosis type I. However, despite significant effort, the role of the HFE protein in iron metabolism is still unknown. To shed a light on the molecular mechanism of HFE-related hemochromatosis we studied protein expression changes elicited by HFE-deficiency in the liver which is the organ critical for the regulation of iron metabolism. We undertook a proteomic study comparing protein expression in the liver of HFE deficient mice with control animals. We compared HFE-deficient animals with control animals with identical iron levels obtained by dietary treatment to identify changes specific to HFE deficiency rather than iron loading. We found 11 proteins that were differentially expressed in the HFE-deficient liver using two-dimensional electrophoresis and mass spectrometry identification. Of particular interest were urinary proteins 1, 2 and 6, glutathione-S-transferase P1, selenium binding protein 2, sarcosine dehydrogenase and thioredoxin-like protein 2. Our data suggest possible involvement of lipocalins, TNF-alpha signaling and PPAR alpha regulatory pathway in the pathogenesis of hereditary hemochromatosis and suggest future targeted research addressing the roles of the identified candidate genes in the molecular mechanism of hereditary hemochromatosis.
Keywords: polymerázová řetězová reakce; Iron; sekvence aminokyselin; spektrofotometrie atomová; Electrophoresis, Gel, Two-Dimensional; Mice, Knockout; železo; Hemochromatosis; Gene Expression; Hemochromatosis Protein; Proteomics; messenger RNA; 2D gelová elektroforéza; RNA, Messenger; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; přetížení železem; myši; Histocompatibility Antigens Class I; myši inbrední C57BL; Polymerase Chain Reaction; hemochromatóza; Iron Overload; Mice; protein hemochromatózy; Proteome; MHC antigeny I. třídy; mužské pohlaví; Spectrophotometry, Atomic; proteom; membránové proteiny; zvířata; játra; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Mice, Inbred C57BL; Liver; Membrane Proteins; Animals; myši knockoutované; exprese genu; molekulární sekvence - údaje; Male; Molecular Sequence Data; Amino Acid Sequence; proteomika